2007
DOI: 10.1007/s10661-007-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of polychlorinated biphenyl contamination and estrogenic activity in water, commercial feed and farmed seafood

Abstract: We evaluated the concentration and congener distribution of seven "target" polychlorinated biphenyls (PCBs) present in water collected in different aquaculture farms of the Mediterranean area, commercial feeds, and farmed seafood. PCBs were present in feed and in tissues of all the analysed organisms at levels ranging from 1.96 ng g(-1) to 124.00 ng g(-1) wet weight, and in 10.5% of the water samples, at levels from under detection limit to 33.0 ng l(-1) with total PCB concentrations significantly higher in sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Some studies have shown that commercial feed is the major contributor for PEP accumulation in cultivated species. PBDEs [31,49], PCBs [45,46], OCPs [31,47], PAHs [31], and heavy metals [53] were reported in feeds, and similar congener profiles between feed and analyzed samples were obtained.…”
Section: Aquaculture Practices As a Source Of Persistent Contaminantssupporting
confidence: 52%
See 1 more Smart Citation
“…Some studies have shown that commercial feed is the major contributor for PEP accumulation in cultivated species. PBDEs [31,49], PCBs [45,46], OCPs [31,47], PAHs [31], and heavy metals [53] were reported in feeds, and similar congener profiles between feed and analyzed samples were obtained.…”
Section: Aquaculture Practices As a Source Of Persistent Contaminantssupporting
confidence: 52%
“…Products from aquaculture are generally regarded as safe and nutritious foods, but sometimes they show a higher risk of contamination by PEPs than that of products from freshwater or marine ecosystems [44]. The concentrations of contaminants may vary depending on the chemical properties of the compound, fish species, physiological state, type of farming, location of the farm, farming technology, management practices, and season [45]. It is usually reported that farmed species contain higher amounts of OCs and heavy metals than wild caught species.…”
Section: Aquaculture Practices As a Source Of Persistent Contaminantsmentioning
confidence: 99%
“…Most have estrogen-like activity or block androgen action [33]. Phthalates are used as plasticizers and are testicular toxins as well as estradiol imitators.…”
Section: Chemical Contaminants Of Formulamentioning
confidence: 99%
“…PCBs bioaccumulate through the food chain. Although the production of PCBs was banned in 1970s, they have been detected in samples of human blood and tissues (Donato et al, 2006;Koopman-Esseboom et al, 1994;Pinto et al, 2008) because of their chemical stability and high lipophilicity. PCB congeners are endocrine disruptors that can cause adverse effects on reproductive, immune, and neurological systems in humans (Carpenter, 1998;Swanson et al, 1995).…”
Section: Introductionmentioning
confidence: 99%